Diagnosis and management of postpancreatectomy hemorrhage: a systematic review and meta-analysis. Issue 8 (August 2019) - Floortje van Oosten, A.; Smits, F. Jasmijn; van den Heuvel, Daniël A.F.; van Santvoort, Hjalmar C.; Molenaar, I. Quintus
Abstract: Background: Postpancreatectomy hemorrhage is a potentially lethal complication after pancreatic resection. The objective of this systematic review is to provide insight in the current status of incidence, detection, management and clinical outcomes of late postpancreatectomy hemorrhage. Methods: A systematic search was conducted on the literature from February 2007 to July 2018 in PubMed, Embase and the Cochrane library. Included were clinical studies with clinical outcomes on late postpancreatectomy hemorrhage defined according to the International Study Group of Pancreatic Surgery definition (i.e. occurring >24 h after pancreatic resection). Results: A total of 14 studies on 467 patients with late postpancreatectomy hemorrhage were included. The incidence of late postpancreatectomy hemorrhage ranged from 3% to 16% (weighted mean: 5%). Seventy-four patients received conservative treatment; 252 patients underwent primary endovascular intervention; 82 patients underwent primary relaparotomy; 56 patients underwent primary endoscopic intervention; and three patients died before any intervention could be performed. CT-scan and diagnostic angiography were able to identify the source of hemorrhage in 67% (66/98) and 69% (114/166) of patients, respectively. The most frequent origin of the hemorrhage was the gastroduodenal artery stump (79/275; 29%), followed by the common hepatic artery (51/275; 19%) and splenic artery (32/275; 12%). Overall mortality was 21% (98/464 patients; range 0%–38%). Mortality was lower after primary interventional angiography as compared to primary relaparotomy (16% vs 37% respectively). Conclusions: This systematic review provides a comprehensive overview of the current literature for severe late postpancreatectomy hemorrhages. CT-scan and diagnostic angiography are equally sensitive in detecting the bleeding source. Interventional angiography appears to be associated to lower mortality as compared to relaparotomy and endoscopy as first intervention for postpancreatectomy hemorrhage.